ANALISIS EFEKTIVITAS PENGGUNAAN ANTIDEPRESAN TERHADAP KUALITAS HIDUP PASIEN DEPRESI DI KLINIK KEJIWAAN X BALIKPAPAN - Diva Nur Fadhila; Dewi Rahmawati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Depression is a medical disorder that can affect thoughts and disrupt psychological well-being, manifesting as feelings of sadness and loss of interest in life, which may impair an individual’s ability to carry out daily activities normally, and in the most severe conditions, depression can lead to suicidal thoughts or ideation. Depression symptoms can be managed using antidepressants, which help balance brain chemistry. This study aims to analyze the effectiveness of antidepressant use on the quality of life of patients with depression at Mental Health Clinic X in Balikpapan. A one-group pre- and post-test design was used, involving 30 patients. Statistical analysis was conducted and presented descriptively. The results indicate that the antidepressant treatment used were not yet fully effective in significantly reducing depression levels, as most patients were still in the early stages of treatment (less than six months). However, the treatment showed considerable effectiveness in improving patients’ quality of life.